"A blank canvas of me": an interpretive phenomenological analysis study of the experience of client self-disclosure in cognitive behavioural therapy for psychosis. Issue 3 (3rd July 2021) - Pipkin, Alastair; Armitage, Dr Sarah; Knight, Matthew; Hogg, Lorna
ABSTRACT: Background : Client disclosure of emotionally salient information to a therapist may be an important factor in the effectiveness of Cognitive Behavioural Therapy for Psychosis (CBTp). The present study explores how people engaging with CBTp make sense of sharing emotionally salient information with a therapist and considers how mental health stigma may influence how participants decide whether to share information. Methods : Eight participants were recruited for semi-structured interviews lasting 30–75 minutes. Interpretive Phenomenological Analysis was used. Results : Two main themes were identified. I am responsible for controlling the negative impact of disclosure refers to participants' awareness that sharing distressing experiences may have negative consequences. Participants worried about being judged, such as being seen as abnormal or having the potential to harm others. They also worried about feeling shamed or distressed. Non-disclosure may be a way of avoiding these fears. The second theme, Therapy makes me feel normal, describes how participants viewed themselves more positively from their therapist validating and understanding their experiences. Conclusions : Internalized stigma-based beliefs may influence self-disclosure, and the therapeutic relationship may provide alternative, positive beliefs about the self as normal. Further research can explore beliefs about self-disclosure and consider micro-affirmations as a therapeutic process.